Strategi Pemasaran dan Pengengembangan Kemasan UMKM Pie Susu Kering Khas Desa Rejoagung - Tyas, Sukma Wahyuning; Winarti, Winarti; Faidah, Amanda; A, Ayu Eka Rizky; Kholis, Nur (CV. ITTC INDONESIA, 2023)
Rejoagung Village is an area located in the Ploso. There are many industries that still home-scale or micro, small and medium enterprises (MSMEs). This service activity collaborates with milk pie business actors. However, business actors experience several obstacles, namely related to marketing and packaging. So that the purpose of this community service activity is to provide training to strategy MSMEs in using social media as digital marketing to introduce products to a wider range of consumers. And also provide training to MSMEs in terms of packaging renewal. The method used in this activity is Assets Based Community Development (ABCD), which is an approach model in community development. The output resulting from this community service activity is that business actors identify and are skilled at marketing through social media as well as updating more attractive packaging.